PERANCANGAN PRIVATE E-MARKETPLACE UNTUK USAHA MIKRO KECIL DAN MENENGAH ( UMKM ) PROVINSI SUMATERA BARAT DENGAN PENDEKATAN INTERAKTIVITAS WEB 2.0 - , WILLY WIZE ANANDA ZEN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Generally, SMEs have a limited market and demand and only attract few customers because of limitations on promotion about their products and services. Thereâs no IT alignment to support business processes and expand market area into global market. This problem occured because most of SMEs are still constrained by financial and technical difficulties to build and develop their IT infrastructure. Private E-Marketplace for SMEs in West Sumatra aims to help SMEs in adopting IT and facilitate SMEs to promote their products and expand market area into global market through the internet. Web 2.0 interactivity approach is expected to bring a new style in E-Marketplace services. The design is done by rapid prototyping method which is expected to create a prototype that covers the management, user, and technology. The results of this research is a web based prototype of Private E- Marketplace which accessible through the Internet. The prototype is expected to help increase productivity of SMEs and also be a recomendation for the government as an alternative in providing IT infrastructure to empower SMEs in West Sumatra.